Zoppot Das Weltbad an der Ostsee - Wiertz, Jupp (1888-1939). (Danzig : [wydawca nieznany], 1937)
Broszura reklamowa Sopotu.
Keywords: 1901-2000; Turystyka; Wolne Miasto Gdańsk (1920-1939); Druki ulotne